Analysis of the readiness of algorithm leadership implementation in the context of performance improvement in East Java Provincial government agencies - Wahyudi, Wahid (Junal Ilmu Manajemen, 2025)
The limitation of efficiency and accuracy in decision-making in East Java Provincial government agencies is a leadership problem caused by the lack of technology and data-based systems. This study aims to determine the level of readiness of East Java Provincial government agencies in implementing algorithm-based leadership. The methodology used in this study is a quantitative approach with data collection techniques through questionnaires distributed to 173 officials in the Regional Apparatus Work Unit (SKPD) of East Java Province. Data analysis used descriptive statistics and correlation tests to identify the relationship between organizational readiness and performance factors. The results of the study show that the level of readiness of government agencies in implementing algorithm leadership is quite good, with factors such as regulations, policies, and infrastructure getting high average scores. However, several aspects still need improvement, especially related to the understanding of algorithmic leadership styles and the continuity of strategic planning during leadership changes. The effect of implementation readiness on improving organizational performance is also significant, especially in terms of fast data processing and more timely decision-making. The suggestions are to enhance the understanding of government apparatus related to algorithm-based leadership, strengthen coordination between institutions, and improve routine training related to information technology infrastructure to support more effective implementation.